Orphan nuclear receptor NR4A1 regulates transforming growth factor-? signaling and fibrosis - Palumbo-Zerr, Katrin; Zerr, Pawel; Distler, Alfiya; Fliehr, Judith; Mancuso, Rossella; Huang, Jingang; Mielenz, Dirk; Tomcik, Michal; Fuernrohr, Barbara G.; Scholtysek, Carina; Dees, Clara; Beyer, Christian; et al. (Nature Medicine, 2015)
Mesenchymal responses are an essential aspect of tissue repair. Failure to terminate this repair process correctly, however, results in fibrosis and organ dysfunction. Therapies that block fibrosis and restore tissue homeostasis are not yet available for clinical use. Here we characterize the nuclear receptor NR4A1 as an endogenous inhibitor of transforming growth factor-? (TGF-?) signaling and as a potential target for anti-fibrotic therapies. NR4A1 recruits a repressor complex comprising SP1, SIN3A, CoREST, LSD1, and HDAC1 to TGF-? target genes, thereby limiting pro-fibrotic TGF-? effects. Even though temporary upregulation of TGF-? in physiologic wound healing induces NR4A1 expression and thereby creates a negative feedback loop, the persistent activation of TGF-? signaling in fibrotic diseases uses AKT- and HDAC-dependent mechanisms to inhibit NR4A1 expression and activation. Small-molecule NR4A1 agonists can overcome this lack of active NR4A1 and inhibit experimentally-induced skin, lung, liver, and kidney fibrosis in mice. Our data demonstrate a regulatory role of NR4A1 in TGF-? signaling and fibrosis, providing the first proof of concept for targeting NR4A1 in fibrotic diseases.
EVALuna2:13097